Antiferroelectric ADP doping in ferroelectric TGS crystals - Arunmozhi, G. (2002)
Crystal growth, morphology, hysteresis and dielectric measurements on 20 mol% ammonium dihydrogen phosphate (ADP)doped triglycine sulphate (TGS) crystals are reported. Crystals grew with morphology similar to phosphoric acid-doped TGS (TGSP). Inhomogeneous incorporation of dopants gives rise to a distribution in coercive fields in the different growth sectors. The incorporated dopant hinders polarization switching, which results in the increase in coercive field. No internal bias field is created by the dopant and the phase transition observed is similar to pure TGSP. The Curie point shifts to a lower temperature with increasing dopant concentration in the growth sectors. Significant changes in the activation energies of annealed specimen were identified.